An Investigation on the Effects of Writing Anxiety on Readiness of Writing among Low Proficiency Undergraduates - Sabariah Abd Rahim; Paramaswari Jaganathan; Tengku Sepora Tengku Mahadi (Penerbit UMP, 2016)
Writing anxiety is a common problem affecting ESL learners’ proficiency. As writing skill is the most difficult skill that needs to be acquired by ESL learners, it is pertinent to manage the anxiety level to encourage learners to write. The facilitative effect of anxiety is important in enhancing writing skills, particularly among low proficiency students. This study investigates the effects of writing anxiety on the readiness towards writing tasks in English among low proficiency undergraduates in Universiti Malaysia Sabah. A total of thirty undergraduates with MUET band 1 or 2 participated in the study. The anxiety level was measured using Second Language Writing Anxiety Inventory (SLWAI). The data showed that students with high cognitive, somatic and avoidance anxiety have a greater apprehension towards writing tasks compared to those with low level of cognitive, somatic and avoidance anxiety. This affects their readiness to do writing tasks in English. This study has implication on the facilitating of classroom practices to enable students to involve and participate more effectively in their writing tasks.